2004
DOI: 10.1111/j.1532-5415.2004.52109.x
|View full text |Cite
|
Sign up to set email alerts
|

A Randomized, Controlled Trial of Doxycycline and Rifampin for Patients with Alzheimer's Disease

Abstract: Therapy with doxycycline and rifampin may have a therapeutic role in patients with mild to moderate AD. The mechanism is unlikely to be due to their effect on C. pneumoniae. More research is needed to investigate these agents.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
151
0
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 207 publications
(157 citation statements)
references
References 27 publications
(65 reference statements)
3
151
0
1
Order By: Relevance
“…These findings indicate that boosting mitochondrial function and proteostasis may decrease the formation of detrimental protein aggregates in the context of proteotoxic disease, typified by reduced mitochondrial activity and loss of proteostasis. Together with initial evidence suggesting potential benefits of targeting dysfunctional mitochondria in AD 2628,40,41 and in view of recent findings linking mitochondrial stress to the induction of cytosolic proteostasis mechanisms 4245 , our data support the concept that enhancing mitochondrial proteostasis may hold promise to manage pervasive Aβ proteopathies, such as AD.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…These findings indicate that boosting mitochondrial function and proteostasis may decrease the formation of detrimental protein aggregates in the context of proteotoxic disease, typified by reduced mitochondrial activity and loss of proteostasis. Together with initial evidence suggesting potential benefits of targeting dysfunctional mitochondria in AD 2628,40,41 and in view of recent findings linking mitochondrial stress to the induction of cytosolic proteostasis mechanisms 4245 , our data support the concept that enhancing mitochondrial proteostasis may hold promise to manage pervasive Aβ proteopathies, such as AD.…”
Section: Discussionsupporting
confidence: 84%
“…5h,i). These results add to observations of in vitro 26 and in vivo studies in AD flies 27 and patients 28 , which suggested that dox treatment may ameliorate AD and Aβ aggregation. Recently, the regulation of the mitochondrial stress responses in mammals, including dox-dependent mitochondrial stress, was shown to rely on the activation of the integrated stress response (ISR) and on the transcription factor ATF4 2931 .…”
Section: Reducing Mitochondrial Translation Lowers Aβ Proteotoxicitysupporting
confidence: 78%
“…It was concluded that use of antibacterial compounds may not have had any effect on the treatment of C. pneumoniae but had a beneficial effect on cognitive decline in AD (193). This might be related to prevention or attenuation of a number of peripheral infections or dampening down the proinflammatory cytokine response.…”
mentioning
confidence: 99%
“…In a study of subjects with mild to moderate AD, a 3-month course of doxycycline and rifampicin reduced cognitive deterioration during a 6 months' follow-up interval (193). It was concluded that use of antibacterial compounds may not have had any effect on the treatment of C. pneumoniae but had a beneficial effect on cognitive decline in AD (193).…”
mentioning
confidence: 99%
“…The olfactory epithelium has been proposed as the primary infectious site and the pathogen seems to reach to the olfactory bulb and olfactory cortex and then neuronal damage may progress (Balin & Appelt, 2001). Long term antibiotic therapy, including doxycycline and rifampin, slowed the course of cognitive impairment (Loeb et al, 2004). Metal protein attenuating compounds have been shown to decrease beta amyloid plaques in animal models and antiprotozoal metal chelator clioquinol was used for treatment (Finefrock et al, 2003, Cahoon, 2009.…”
Section: Chlamydia and Neurologic Disordersmentioning
confidence: 99%